2008
DOI: 10.1057/jt.2008.6
|View full text |Cite
|
Sign up to set email alerts
|

Are the shoes appropriate to wear?: A study of cohort values

Abstract: an associate professor at the West Chester University of Pennsylvania, earned her PhD in Marketing from Kent State University. Prior to earning her degree she held a variety of positions in market research fi rms. Her current research interest focuses on segmentation and service quality and how these factors infl uence a company ' s ability to extract value from its consumer base. Keywords segmentation , cohort analysis , Baby Boomer , age , consumer behaviourAbstract This study investigates the values differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Generation Y consumers tend to respond well to humorous messages, satire and honesty (Syrett and Lammiman, 2004). Generation Y consumers value fun, excitement and enjoyment both in advertising and consumption experiences more so than previous cohorts (Arsenault and Patrick, 2008). Moore and Carpenter (2008) found that they enjoy shopping and the whole purchase experience more so than previous generations.…”
Section: Integrated Marketing Communications (Imc)mentioning
confidence: 85%
“…Generation Y consumers tend to respond well to humorous messages, satire and honesty (Syrett and Lammiman, 2004). Generation Y consumers value fun, excitement and enjoyment both in advertising and consumption experiences more so than previous cohorts (Arsenault and Patrick, 2008). Moore and Carpenter (2008) found that they enjoy shopping and the whole purchase experience more so than previous generations.…”
Section: Integrated Marketing Communications (Imc)mentioning
confidence: 85%
“…The purchase behaviour of different generational cohorts is found to vary according to their product preferences (Dann, 2007) for beverages (Rentz et al, 1983), motion pictures (Holbrook and Schindler, 1989), automobiles (Braun-LaTour et al, 2007), formal and informal attire (Arsenault and Patrick, 2008) and travel (Lehto et al, 2008). Rodriguez (1993) found that the purchasing power of middle and lower socioeconomic cohorts of Peruvians was influenced by their degree of religiosity.…”
Section: Theory and Conceptual Developmentmentioning
confidence: 99%
“…The Boomer I cohort still heavily values its individualism (remember, they were and are the ''Me'' generation). And, compared to the later cohorts, the Generations X and Y, Boomer Is have been found to be significantly different in terms of valuing self-respect and a sense of accomplishment (Arsenault & Patrick, 2008). These are important differences when medical staff relationships come into play within health care organizations.…”
Section: Boomers I Cohort: the Leading-edge Boomersmentioning
confidence: 96%
“…To date they have been hopeful of the future. Compared to other cohorts, they place more value on excitement, fun, and enjoyment (Arsenault & Patrick, 2008). Already health care incomes are not what they used to be, what with malpractice insurance and insurance claim payment ceilings.…”
Section: Boomers II Cohort: the Trailing-edge Boomersmentioning
confidence: 99%